2012
DOI: 10.1177/0266666912438567
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extrinsic and intrinsic motivation on knowledge sharing intentions of civil servants in Ebonyi State, Nigeria

Abstract: This study investigated the effect of attitude on employee knowledge sharing intentions and examined the effect of extrinsic and intrinsic motivation on employee attitude and intention toward knowledge sharing. To understand the motivators of employee knowledge sharing intentions, a modified Theory of Reasoned Action (TRA) was adopted. Specifically, extrinsic and intrinsic motivations contexts were considered as factors that affect employee attitude and intentions toward knowledge sharing. The descriptive surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 49 publications
11
79
0
1
Order By: Relevance
“…Contrary to the perceived positive effect of rewards and incentives, Chang et al (2007) showed that outcome-based rewards and sufficient rewards for effort did not foster knowledge sharing among product development team members. Olatokun and Nwafor (2012) also found that expected organizational rewards did not significantly influence employee attitudes and intentions toward knowledge sharing.…”
Section: Key Determinants Of Knowledge Sharing In the Public Sectormentioning
confidence: 89%
“…Contrary to the perceived positive effect of rewards and incentives, Chang et al (2007) showed that outcome-based rewards and sufficient rewards for effort did not foster knowledge sharing among product development team members. Olatokun and Nwafor (2012) also found that expected organizational rewards did not significantly influence employee attitudes and intentions toward knowledge sharing.…”
Section: Key Determinants Of Knowledge Sharing In the Public Sectormentioning
confidence: 89%
“…It is influenced mainly by two factors which are the attitudes of individuals directed to an object or group and a subjective standard that relates to the individual's perception about people who consider important, responding to a particular behavior [21]. Also in the field of knowledge management, the model of the Theory of Planned Behavior is used to analyze the intentions of the employee to share tacit knowledge [25]. Moreover, the Theory of Reasoned Action [26], assumes that people react to certain behavior when they are motivated and perceive more benefits, thereby increasing their intent to participate [17].…”
Section: Theorical Foundationmentioning
confidence: 99%
“…Sharing knowledge is a major challenge for organizations and has forced them to pay more attention to the implementation of strategies to capture that knowledge for the many advantages which represents them, because when that knowledge is not shared, run the risk of losing it, especially when the employee leaves the workplace, causing costs to the company [25].…”
Section: Intention To Sharing Tacit Knowledgementioning
confidence: 99%
“…Analysis of the above results suggests that reward system is a critical tool to implement KM strategies in the KSA construction organisations. But the problem with many reward systems and incentives for sharing knowledge is that useful knowledge comes from the lower cadre in the organisation, from people who are not on incentive systems and probably respond much more readily to the feeling that they belong to highly motivated, leading edge, innovative groups of people (Olatokun and Nwafor 2012).…”
Section: Sharing Knowledgementioning
confidence: 99%